PROGRAM DANA HIBAH DALAM PERSPEKTIF POLITIK DISTRIBUTIF: STUDI KASUS PRODAMAS KOTA KEDIRI - Wimmy Haliim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2019)
The concept of public policy is present and develops as an instrument for the state that aims to prosper the people. In Kediri, there was a public policy called Prodamas. Prodamas is a grant program that is actually presented by the Kediri City government to increase community participation in infrastructure and human development in the City of Kediri. But with a distributive political perspective, Prodamas is seen as a political tool for incumbents, Abdullah Abu Bakar. The indicator, the incumbent campaign program for the Kediri City elections in 2018 is to increase the number of Prodamas funds up to twice (Prodamas Plus), although in practice Prodamas still has many implementation problems. Secondly, the Socialization of Prodamas Plus has been socialized long before the momentum of the Kediri 2018 regional election. Third, Prodamas social assistance which is only given to a number of Kelurahan without clear indicators. Fourth, Prodamas have similarities with other participatory development mechanisms, namely 'Planning and Development Consultation' (Musrenbang). From these indicators, the authors conclude that Prodamas is not only a public policy that is only present for the welfare of the community, but incumbents political tool for political interests in the Kediri City elections 2018. Key Words: Political Distributive, Public Policy, Prodamas, and Incumbent.